Seasonal Variation of Food composition and Feeding Activity of Small Adult Barramundi (Lates calcarifer, Bloch) in the South west Coastal Water near Khulna, Bangladesh - Mushahida-Al-Noor, Syeda; Kamruzzaman, Sheikh; Hossain, Md. Delwer (Our Nature, 2013)
The food habits of juvenile Lates calcarifer in the Shibsha river were investigated by examining the gastro-intestine contents of 720 specimens collected from June, 2010 to July, 2011. The major component of the diet was teleosts were dominant (32.40%) found in the stomach of Lates calcarifer. The next major food group were macro-crustacean (22.65%), followed by zooplankton (17.16%), algae (10.40%) and insects (9.89%). Monthly fluctuations were also witnessed in the percentage occurrence of stomachs with different degrees of fullness. It is evident that higher percentage of fullness of the stomach was recorded in pre-monsoon due to pre-spawning fattening process. Higher percentage of emptiness of the stomach was recorded in monsoon, due to starvation during breeding seasons. It is also observed that the percentage of stomach fullness was higher in summer than the percentage in winter in juvenile L. calcarifer.. DOI: http://dx.doi.org/10.3126/on.v10i1.7772